Sociocultural Determinants to Adoption of Safe Water, Sanitation, and Hygiene Practices in Nyakach, Kisumu County, Kenya: A Descriptive Qualitative Study. (8th December 2016) - Wasonga, Job; Okowa, Mark; Kioli, Felix
Abstract : Provision of safe water, adequate sanitation, and hygiene has been lauded as one way of preventing diarrheal infections and improving health especially in developing countries. However, lack of safe water, inadequate sanitation, and poor hygiene practices in most parts of rural Kenya have posed a challenge that exposes the populace to diarrhea cases and possible deaths. In this regard, many nongovernmental organizations and governmental agencies have tried to provide water, sanitation, and hygiene services with poor results. This study was conducted using qualitative research methods in Central Nyakach in Kisumu County, Kenya. The methods were focus group discussions (FGD), key informant interviews (KII), and observation of homesteads. The data were then analyzed thematically. Findings revealed that water issues are gendered and its use is socially and culturally categorized. Water storage is affected by traditions such as use of a clay pot, while sanitation and hygiene issues are ritualized and bound by taboos. Latrines are majorly constructed by men and sharing the same with in-laws and older children is prohibited. Children faeces are thrown out in the open fields as a means of disposal and hand washing with soap is nonexistent, since it is believed that doing so would make a person lose the ability to rear livestock. The implications of these findings are that some of these sociocultural practices have a profound effect on health of the population. This affects health care delivery through high incidence rates of disease, encourages "unhealthy" environments through open defecation and pollution, and negates the government's commitment to national and international policies on universal health care provision.